MAINSTREAMING CALENDAR RITES IN MUSEUMS OF KEMEROVO REGION - T. I. Kimeeva; P. V. Glushkovа (Вестник Кемеровского государственного университета, 2014)
Traditional calendar rites is one of the most important layers of the intangible cultural heritage. In the context of globalization and informatization, this phenomenon is the most exposed to destruction. In modern conditions, we can observe the loss of traditions relating to the field of the ethnic calendar. It is thus urgent not to record these traditions, but to include them in the current environment. One of the leading roles in this area belongs to the museum. Despite the fact that museums are today actively presenting calendar rites as part of the intangible heritage, the methodological basis of such museum activities is poorlydesigned. The lack of a theoretical framework leads to the violation of the principles of museum work and distortion of folk tradition. In this paper, we propose some uniform methods, principles, forms of mainstreaming the calendar rite within the museum's activities. Based on the analysis of existing experience, this will contribute to the revitalization of a significant reservoir of intangible heritage of the Russian and the indigenous population of Kemerovo region.